Accelerated Skills Acquisition Protocol (ASAP) in optimizing robotic surgical simulation training: a prospective randomized study - Gurung, Pratik M. S.; Campbell, Timothy; Wang, Bokai; Joseph, Jean V.; Ghazi, Ahmed E. (World journal of urology, 2020)
Purpose To assess the efficacy of an accelerated proficiency-based training protocol in robotic simulation practice in delivering durable proficiency compared to conventional training methods. Methods Novice medical students ( n = 16) were randomized into either the accelerated skills acquisition protocol (ASAP) or conventional training protocol (CTP). Subjects were trained to proficiency on the da Vinci Skills Simulator (dVSS) by an expert trainer. Differences in the repetitions required to achieve proficiency in two simple and two complex virtual reality (VR) training tasks were assessed as the primary outcome measure. Transfer of the acquired skills to two other non-practiced tasks was assessed immediately and prospectively followed through to 3, 6 and 12 months in the two groups. Retention of the practiced tasks was assessed along the same timeframe. Results Subjects in the ASAP group acquired proficiency significantly faster in three of the four training tasks: camera control ( p = 0.0002), suture sponge ( p < 0.0001), ring walk3 ( p < 0.0001), and peg board ( p = 0.6936). When assessing transfer of skills, there were no significant differences between the two groups: Ring rail 3 ( p = 0.6807) and Tubes ( p = 0.2240). When assessing retention of skills at 3, 6 and 12 months, for all 6 tasks, no significant differences were seen between the ASAP and CTP groups. Conclusion ASAP is proven to be an efficient approach for delivering proficiency in robotic VR simulation training. The results are durable when compared to conventional simulation training methods. The findings may have significant implications in the design of robotic VR simulation curricula.